Understanding The Influencing Factors in The Onset of PCOS: A Review - Kurniawati, Erna Yovi (Jurnal Keperawatan Komplementer Holistic, 2025)
Polycystic ovary syndrome (PCOS) is an endocrine disorder prevalent in women of reproductive age. This comprehensive review aims to shed light on the various factors that contribute to the onset and progression of PCOS. The analysis includes a thorough exploration of genetic predisposition, environmental influences, and lifestyle factors in the context of their role in the hormonal dysregulation, insulin resistance and ovarian dysfunction associated with PCOS. The complex relationship between these factors and the clinical manifestations of PCOS, including irregular menstrual cycles, hyperandrogenism, and polycystic ovarian morphology, is also discussed. By synthesizing current research findings, this review provides a comprehensive understanding of the various factors that influence the occurrence of PCOS, offering valuable insights for reference in reproductive health education, early detection of PCOS, and development of comprehensive prevention and intervention combinations.